Multiple tributes have been received by the teacher Kurz on the occasion of her eightieth birthday - ., Sociedad Mexicana de Ingeneiria Biomedic (Revista Mexicana de Ingenieria Biomedica, 2018)
The main event was organized by the Mexican Physics Society and was held in the auditorium of the Faculty of Sciences of the UNAM; During the seminar, Professor Kurz's valuable contribution to the development of Cybernetics was emphasized, as well as the constant encouragement she has given to young people interested in this discipline, as well as her dedication to teaching and university problems.